Determining the maximum information gain and optimizing experimental design in neutron reflectometry using the Fisher information. Issue 4 (7th July 2021) - Durant, James H.; Wilkins, Lucas; Butler, Keith; Cooper, Joshaniel F. K.
Abstract : A framework is developed using the Fisher information for information quantification in neutron reflectometry. The framework's utility is demonstrated in the rapid estimation of model parameter uncertainties, as well as in experimental design to maximize information gain about given systems. Abstract : An approach based on the Fisher information (FI) is developed to quantify the maximum information gain and optimal experimental design in neutron reflectometry experiments. In these experiments, the FI can be calculated analytically and used to provide sub‐second predictions of parameter uncertainties. This approach can be used to influence real‐time decisions about measurement angle, measurement time, contrast choice and other experimental conditions based on parameters of interest. The FI provides a lower bound on parameter estimation uncertainties, and these are shown to decrease with the square root of the measurement time, providing useful information for the planning and scheduling of experimental work. As the FI is computationally inexpensive to calculate, it can be computed repeatedly during the course of an experiment, saving costly beam time by signalling that sufficient data have been obtained or saving experimental data sets by signalling that an experiment needs to continue. The approach's predictions are validated through the introduction of an experiment simulation framework that incorporates instrument‐specific incident flux profiles, and through the investigation of measuring the structural properties of a phospholipid bilayer.